Study guides

☆☆

Q: What is x squared plus 12x plus 36 equals?

Write your answer...

Submit

Still have questions?

Related questions

x2+12x+36=0 2x+12x+36=0 14x+36=0 14x=-36 x=-36/14 x=-2 4/7

This is not an inequality. This is an equation.12x+7=43 12x=36 x=3

x=5/2*sqr(3)

x2-12x+36 = (x-6)2

=>2x - 12x + 36 = 0 =>10x = 36=>x = 3.6Another contributor's answer:This is a quadratic equation question:x2-12x+36 = 0When factorised:(x-6)(x-6) = 0

x^2 + 12x = 5 x^2 + 12x + __ = 5 + __ x^2 + 12x + 36 = 5 + 36 (The 36 I got from taking half of 12 and then squaring that number (which is 6).) (x + 6)^2 = 41 x + 6 = (the square root of 41) x = (the square root of 41) - 6. Hope that helped :)

x = plus or minus 6.

Depending on whether or not there are implied brackets: x + 62 = x + 36 (x + 6)2 = x2 + 12x + 36

62 = 36

x = Â±2

The graph is a circle with a radius of 6, centered at the origin.

6 squared is 36. 36 plus 3 is 39

3060.

It is: 36 plus 121 = 157

36. 02 = 0 62 = 36

Six

6 squared = 6*6 = 36

If by d2 you mean d squared then it is non linear

36. 4 squared is 16...16 + 20 - = 36.

x^2 + 12x + 36 = 0(x + 6)(x + 6) = 0(x + 6)^2 = 0√(x + 6)^2 = ± √0x + 6 = 0x + 6 - 6 = 0 - 6x = 6

Because 6 squared equals 36 and 36 terminates, or ends, which makes it rational.

We have 3x+9y=36, or equivalently 12x+36y=144. We also have 12x+4y=18, so subtracting these we have 32y=126 or y=63/16. Substituting this into our original equation leaves 3x=36-9*63/16 or x = 12-3*63/16 = 3/16. So: x=3/16, y=63/16

12x = 36

If you're looking to solve for x, you can do so as follows: x2 + 12x - 6 = 0 x2 + 12x + 36 = 42 (x + 6)2 = 42 x + 6 = ± √42 x = -6 ± √42

62